A core-sheath holey graphene/graphite composite fiber intercalated with MoS2 nanosheets for high-performance fiber supercapacitors. (10th May 2019) - Wang, Chaojun; Zhai, Shengli; Yuan, Ziwen; Chen, Junsheng; Zhang, Xinshi; Huang, Qianwei; Wang, Yanqing; Liao, Xiaozhou; Wei, Li; Chen, Yuan
Abstract: One-dimensional fiber-shaped supercapacitors have recently attracted lots of attention as a potential energy storage solution for emerging wearable devices. However, fiber supercapacitors often exhibit low energy storage capacity and poor rate capability due to their small volume, low specific volumetric capacitance, and poor electrode electrical conductivity. Here we demonstrate a novel hydrothermally assembled core-sheath fiber comprised of a graphite fiber core and a MoS2 nanosheet intercalated holey graphene oxide (HGO) sheath as electrodes for fiber supercapacitors. HGO and MoS2 nanosheets self-assemble around the graphite fiber core in a space-confined reactor during the hydrothermal synthesis. HGO nanosheets supply abundance channels for electrolyte ion transfer, MoS2 nanosheets provide large pseudocapacitance, and graphite fibers serve as faster electron transfer highways. The mass loading of MoS2 is easily tunable. The optimized composite fiber with 34.9 wt% MoS2 delivers a high volumetric capacitance 421 F cm −3  at the CV scan rate of 5 mV s −1 and the capacitance retention of 51.0% when the scan rate increases from 2 to 100 mV s −1 . The core-sheath fiber enables fast reversible redox kinetics, and its surface capacitive energy storage contributes ∼75–80% of its total energy storage. The assembled solid-state fiber supercapacitor delivers a high device volumetric capacitance of 94 F cm −3  at 0.1 A cm −3 and an energy density of 8.2 mWh cm −3  at the power density of 40 mW cm −3, outperforming many recently reported fiber supercapacitors. The core-sheath fiber electrode design based on HGO, MoS2 and graphite fiber cores provides an efficient platform for designing various novel fiber electrodes for potential electrochemical applications. Graphical abstract: Image 1 Highlights: A core-sheath fiber contains a graphite fiber core and a sheath made of holey graphene and MoS2 nanosheets. Holley graphene supplies abundance channels for electrolyte ion transfer. Fiber electrodes deliver a high capacitance of 421 F cm −3 and excellent rate capability. Surface capacitive energy storage contributes ∼75–80% of the total energy storage. A fiber supercapacitor provides an energy density of 8.2 mWh cm −3  at a power density of 40 mW cm −3 .